Duloxetine for the treatment of generalized anxiety disorder: a review - Ahsan Y Khan (Dove Medical Press, 2008)
Ahsan Y Khan, Matthew MacalusoDepartment of Psychiatry and Behavioral Sciences, University of Kansas School of Medicine-Wichita, Wichita, KS, USAAbstract: Approximately 16 million people in the United States suffer from anxiety disorders alone, while another 12 million experience both anxiety and at least one other psychiatric condition. Generalized anxiety disorder (GAD) has lifetime prevalence rates between 5% and 6%. Treatment of GAD is aimed primarily at symptom reduction. Duloxetine, a serotonin norepinephrine reuptake inhibitor (SNRI), received Food and Drug Administration (FDA) approval for the treatment of GAD in 2007. This article reviews the pharmacologic profile and seminal clinical trials associated with the FDA indication of duloxetine for GAD. A literature search performed using PubMed with the keywords “duloxetine”, “gad”, “generalized anxiety disorder”, and “venlafaxine XR” yielded 27 articles. We also focused on papers that pooled data from these seminal studies. Data on file from Eli Lilly were also reviewed, including data from the Eli Lilly website. Based on this search, duloxetine was found to be an FDA-approved treatment option for GAD that has been studied in several double-blind, placebo-controlled clinical trials. This review of duloxetine will help physicians to interpret clinical studies properly and also help them to make an informed decision about which patients are the most appropriate candidates for a trial of duloxetine.Keywords: duloxetine, generalized anxiety disorder, clinical trials, serotonin norepinephrine reuptake inhibitor (SNRI)